Prevalence of minimally invasive facial cosmetic surgery and its association with mental health among college students in Kuwait - Alawadhi, Eiman; Ibrahim, Dina; Saadallah, Aishah; Awada, Zainab (Frontiers in Public Health, 2025)
BackgroundMinimally Invasive Facial Cosmetic Surgery (MIFCS), which includes Botox and filler injections, is gaining popularity as a less invasive alternative to classic cosmetic procedures. Previous research has shown that psychological factors such as depression, anxiety, and self-esteem influence the decision to undergo MIFCS. This study aims to assess the relationship between mental health and undergoing MIFCS among undergraduate students attending Kuwait University (KU).MethodsWe investigated the association between MIFCS and mental health variables in KU undergraduates. A cross-sectional design was employed to collect data from all 15 colleges at KU via an online questionnaire using convenience sampling. The study was approved by the Health Science Center (HSC) Center ethics committee at KU and Ministry of Health (MOH) in 9th of January 2025.ResultsA total of 744 students participated, of whom 153 (20.6%) reported undergoing MIFCS. Across the entire sample, 64.4% reported having levels of depressive symptoms, 68.8% reported levels of anxiety symptoms, and 12.6% had low self-esteem. Factors associated with higher odds of MIFCS included being female (aOR 4.01, 95% CI 1.98–8.24), age over 20 years (aOR 4.20, 95% CI 2.47–7.16), being married (aOR 2.38, 95% CI 1.32–4.29), a history of physical disorders (aOR 1.77, 95% CI 1.11–1.66), a family history of mental disorders (aOR 1.87, 95% CI 1.06–3.31), and anxiety symptoms (aOR 2.27, 95% CI 1.42–3.64). In contrast, studying at the Health Sciences Center was associated with lower odds of MIFCS (aOR 0.44, 95% CI 0.25–0.76).ConclusionThe findings highlight the multifaceted nature of MIFCS and its substantial association with mental health issues among undergraduate students. Gender, age, marital status, and a personal or family history of physical and mental health disorders, particularly anxiety, are all key risk factors. Conversely, enrollment in medical disciplines was associated with lower odds of undergoing MIFCS. These findings highlight the importance of including mental health support and psychotherapy in clinical practices to offer holistic care for students’ well-being.